2021
DOI: 10.1101/2021.10.07.21264420
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No difference in retinal fluorescence after oral curcumin intake in amyloid proven AD cases compared to controls

Abstract: INTRODUCTION: Previous work showed in-vivo presence of retinal amyloid in AD patients using curcumin. We aimed to replicate these findings in an amyloid biomarker confirmed cohort. METHODS: Twenty-six AD patients (age 66 (+9), MMSE>17) and 14 controls (age 71(+12)) used three curcumin formulations: Longvida, Theracurmin and Novasol. Plasma levels were determined and pre- and post- curcumin retinal scans acquired using autofluorescence imaging. Images were both visually and quantitatively assessed. RESULTS… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Methodological differences in curcumin protocols and quantification may explain the varied findings (Table 1). Ngolab et al (29) theorized that the higher RAC they found compared with Koronyo et al may have been due to higher curcumin dosing over a shorter period, whereas results from den Haan et al (31) suggest that curcumin uptake may vary. In addition, the retina's inherent autofluorescence may mask the curcumin signal.…”
Section: Curcumin Fluorescencementioning
confidence: 91%
See 1 more Smart Citation
“…Methodological differences in curcumin protocols and quantification may explain the varied findings (Table 1). Ngolab et al (29) theorized that the higher RAC they found compared with Koronyo et al may have been due to higher curcumin dosing over a shorter period, whereas results from den Haan et al (31) suggest that curcumin uptake may vary. In addition, the retina's inherent autofluorescence may mask the curcumin signal.…”
Section: Curcumin Fluorescencementioning
confidence: 91%
“…Although the abovementioned studies strongly suggest the presence of retinal Ab in AD and associations between retinal Ab and cognition and/or AD pathology in the brain, den Haan et al (31) found no differences in retinal fluorescent signals between patients with biomarker positive AD and NCs using 3 formulations of oral curcumin. In participants who received the standard formulation (Longvida, Verdure Sciences, Noblesville, IN), quantitative assessment revealed no difference in hyperfluorescence between biomarkerpositive AD participants and NCs.…”
Section: Curcumin Fluorescencementioning
confidence: 98%